2013
DOI: 10.1007/s11605-013-2150-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Splenectomy and Esophagogastric Devascularization for Bleeding Varices or Severe Hypersplenism: a Comparative Study

Abstract: The short-term effects of laparoscopic splenectomy and esophagogastric devascularization were better than those for open surgery, and the medium-term effects were similar between these two surgical approaches. Prospective randomized studies with a greater number of cases are needed to confirm the role of laparoscopy in splenectomy and esophagogastric devascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…There is no incision in LS + ED, so it is minimally invasive and cosmetology is better. Our previous study 10 showed that there are better short-term effects of minor trauma, quicker recovery, and less complications in LS + ED, and the mediumor long-term effects of controlling EGVB, eliminating hypersplenism, and improving liver function were similar between the two surgical methods. In our institute, the numbers of patients with liver cirrhosis and PH who chose LS + ED in the most recent 5 years have increased year by year.…”
Section: Discussionmentioning
confidence: 88%
“…There is no incision in LS + ED, so it is minimally invasive and cosmetology is better. Our previous study 10 showed that there are better short-term effects of minor trauma, quicker recovery, and less complications in LS + ED, and the mediumor long-term effects of controlling EGVB, eliminating hypersplenism, and improving liver function were similar between the two surgical methods. In our institute, the numbers of patients with liver cirrhosis and PH who chose LS + ED in the most recent 5 years have increased year by year.…”
Section: Discussionmentioning
confidence: 88%
“…Devascularization of the lower esophagus and upper stomach with splenectomy (Hassab’s operation) using laparoscopic or hand-assisted laparoscopic surgical techniques has been reported mainly from Japan and China as surgical therapy for esophagogastric varices [2] , [3] , [4] , [5] , [6] , [7] . However, reports of a surgical approach to this condition while preserving the spleen are rare [8] , [9] , [10] .…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports of laparoscopic or hand-assisted laparoscopic surgery for esophago-gastric varices [2] , [3] , [4] , [5] , [6] , [7] , but operative procedures without splenectomy have rarely been reported [8] , [9] , [10] . We previously performed devascularization of the proximal stomach in a limited area without splenectomy as an open procedure to reduce the invasiveness of the operation compared to Hassab’s operation, and obtained acceptable result [12] .…”
Section: Introductionmentioning
confidence: 99%
“…The gastric coronary vein was visualized and its branches toward the esophagus and proximal stomach were divided near the esophagus and stomach walls with a harmonic scalpel (Figure 2(b)). At least, the distal esophagus (6-10 cm) was dissected through the hiatus, and the paraesophageal venous collaterals were divided [7, 12, 24, 25] (Figure 2(c)). …”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, with the advances of laparoscopic techniques, laparoscopic surgery has been commonly utilized in clinical practices. Nowadays, increasing studies have been focusing on evaluating the safety and feasibility of LSD in esophageal varices and hypersplenism secondary to cirrhosis and portal hypertension [24, 710]. Compared with open surgery, LSD can alleviate postoperative pain and contribute to the recovery of bowel function and feeding.…”
Section: Introductionmentioning
confidence: 99%